Russia’s Modern Banking Law - Dmitry Nefedov (Право. Журнал Высшей школы экономики, 2014)
In this study, the author offers a very general review of banking legislation in Russia. The author discusses the main statutory acts which regulate banking activity and the Central Bank of the Russian Federation (Bank of Russia). The author describes the Bank of Russia’s functions. He concludes that, in modern market conditions, it is extremely important to develop civil regulation and reduce administrative regulation; however, he finds that, unfortunately, the Bank of Russia is still subject to administrative management. Considering the nature of the relationships between the Bank of Russia and private credit organizations, the author insists on the need for a partnership, forged on principles of dispositive regulation, between them. More generally, this work considers the problems of domestic financial regulation through the theoretical prism of free banking. Current Russian banking legislation only focuses on the creation of the best mechanism for the organization of credit and financial relationships. The author considers not only the requirements for state financial policy, but also the interests of private credit organizations, which serve as the engine of the financial market and strengthen the banking system as a whole. Until recently, many aspects of the Russian banking system have been a compromise between the old and new conceptions of the economy. For this reason, the upholding of free market ideas is essential in order to develop banking legal theory. The author criticizes the emerging tendency to reduce the role of liberal financial institutions, such as the increasing role of the Bank of Russia as a mega-regulator. Considering this, the author recommends the application of immediate counteractions against the above-described tendency and supports the strengthening of the independence of credit organizations. He emphasizes that this is the only approach to fully develop the existing banking system.